Une peur perdue : la nuit sombre - Kahia, Béchir (Romanica Silesiana)
The contemporary novel seeks to revive cosmic obscurity and the fear it arises. Its, therefore, opposes electricity that has put an end to such obscurity, and also stands against romantic night as produced by poets. Such writers, like Jean Giono and Henri Bosco, have been able to redeem to the night its majesty and weight. They have, indeed, a vision which construes night as a counter-force to the current estrangement of modern times. The night usually overflows the day and effaces its light during unclear weather or when a tempest produces somber greenness. The character adopts Dionysian attitude, simultaneously drowning into chaos. Writing enables one to hear the night’s whisper. It transits smoothly from clarity to obscurity, from soft events to terrible ones. Key words: Bosco, Giono, night, fear, darkness, writing